The effect of digital marketing and online payment systems on customer purchase intention - Ida Nyoman Basmantra; I Made Wira Arta Kusuma (Review of Management, Accounting, and Business Studies, 2020)
CV Tanteri Ceramics, Pejaten, Tabanan Regency which is engaged in the production of ceramics must provide excellent service that is affordable to consumers in various places, then it is applied marketing methods with digital marketing and online payment methods. The purpose of this study was to determine the effect of Digital Marketing and Online Payment Systems on Consumer Purchase Interest. By using a purposive random sampling technique 15 research samples were taken. Data processing was performed using the classic assumption test, multiple linear regression analysis, F simultaneous test, partial t-test, and the coefficient of determination with the help of the SPSS program. The results of the study: (1) Digital Marketing has a positive effect on Consumer Purchase Interest, which can be seen from the significance level of 0.001, which is less than 0.05; (2) Online Payment System has a positive effect on Consumer Purchase Interest, it can be seen from the significance of 0.031 which is less than 0.05; (3) Digital Marketing and Online Payment Systems simultaneously have a positive effect on Consumer Purchase Interest, which can be seen from the significant 0.000, namely less than 0.05. Suggestions that can be given from the results of this study are the management of Pejaten Ceramic Tabanan Tanteri, Tabanan Regency should make policies or regulations related to marketing, and how to pay online to increase the purchasing power of consumers in the Pejaten Ceramic Tanteri CV Tabanan Regency.